Analysis the Impact of ChatGPT Usage on Student Learning Productivity in Surakarta City: Analisis Dampak Penggunaan ChatGPT terhadap Produktivitas Belajar Siswa di Kota Surakarta - Sari, Dhany Efita; Yudhanto, Rayhan (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the impact of using ChatGPT on student learning productivity in Surakarta. ChatGPT is increasingly popular among students, especially in Surakarta, as a tool to help them complete their assignments. This study was created to fulfill the need for information about the influence of the use of ChatGPT in the educational environment, especially universities in Surakarta. Although it offers convenience because it can access information very quickly, there are concerns that the use of this technology can inhibit students' critical thinking and plagiarism. This study used a qualitative approach with data collection techniques through observation and in-depth interviews with students from various universities in Surakarta. The data collected from the results of the analysis of the experiences and challenges in using ChatGPT when doing learning activities. The results show that the use of ChatGPT produces a positive impact on learning productivity, especially to facilitate finding information. However, there are also negative impacts, namely, it can trigger a decrease in creativity and a decrease in the level of critical thinking of students. The results of this study are expected to help provide information that the use of ChatGPT or other artificial intelligence is not always bad for education, it must be further socialized for future technologies that can be useful for the advancement of Indonesian education.